Effect of Universal Adhesive and Different Surface Pretreatments on Shear Bond Strength of Orthodontic Brackets to Amalgam Restorations: A Comparative Experimental Study - Tahmasbi, Soodeh; Badiee, Mohammadreza; Fahiminejad, Nastaran; Daneshvar , Negar (Journal of Dental School, 2021)
Objectives Many adult patients requiring orthodontic treatment have posterior restorations. Bracket bonding to dental restorations is a clinical challenge. The aim of this study was to compare the effect of universal adhesive with the conventional method on shear bond strength (SBS) of orthodontic brackets to amalgam restorations. Methods Ninety cavities were filled with admixed amalgam and divided into six groups (n=15) according to the surface pretreatment (no mechanical preparation, diamond bur preparation, and sandblasting) and type of bonding agent (alloy primer plus Transbond XT or universal adhesive). Mandibular central incisor brackets were bonded to the restoration surfaces. The primary outcome was the bond strength in megapascals (MPa) which was compared by two-way ANOVA. The mode of failure was the secondary outcome determined by determination of the adhesive remnant index (ARI). The Kruskal-Wallis and Mann-Whitney tests were used to compare the ARI scores among the groups. Results Among the groups with the conventional method, the sandblasted subgroup showed the highest SBS (P<0.05). The three subgroups of universal adhesive were not significantly different in terms of SBS (P=1). Overall, the highest SBS was noted in the sandblasted/conventional adhesive group. Conclusion The results demonstrated that sandblasting plus alloy primer and Transbond XT bonding agent could be recommended for bracket bonding to amalgam restorations. Further studies using other bonding agents are recommended